Modeling the effect of tat inhibitors on HIV latency - Aguilera, Luis U.; Rodríguez-González, Jesús (Journal of theoretical biology, 2019)
Even in the presence of a successful combination therapy stalling the progress of AIDS, developing a cure for this disease is still an open question. One of the major steps towards a cure would be to be able to eradicate latent HIV reservoirs present in patients. During the last decade, multiple findings point to the dominant role of the viral protein Tat in the establishment of latency. Here we present a mathematical study to understand the potential role of Tat inhibitors as virus-suppressing agents. For this aim, we implemented a computational model that reproduces intracellular dynamics. Simulating an HIV-infected cell and its intracellular feedback we observed that removing Tat protein from the system via inhibitors resulted in a temporary and reversible viral suppression. In contrast, we observed that compounds that interact with Tat protein and disrupt the integrated viral genome produced a more permanent viral suppression.
Gesehen am 13.06.2019